Photoluminescence shift in frustules of two pennate diatoms and nanostructural changes to their pores. (3rd March 2014) - Arteaga‐Larios, Nubia V.; Nahmad, Yuri; Navarro‐Contreras, Hugo R.; Encinas, Armando; Viridiana García‐Meza, J.
ABSTRACT The diatom silicified cell wall (frustule) contains pore arrays at the micro‐ to nanometer scale that display efficient luminescence within the visible spectrum. Morphometric analysis of the size and arrangement of pores was conducted to observe whether any correlation exists with the photoluminescence (PL) of two diatom species of different ages. UV‐excited PL displays four clearly defined peaks within the blue‐region spectrum, on top of the broad PL characteristic of synthetic porous silicon dioxide, recorded for reference and where discrete lines are absent. A set of shifted emission lines was observed when diatom cultures reached adulthood. These discrete line shifts correlate with structural changes observed in adult frustules: reduction in pore diameter; appearance of pores within pores, 10 nm in size; an increase in the gap distance between stria; and the deposition of several girdle bands with a concomitant increase in the diatom waist length, as well as the appearance of pores on such bands. Destruction of the pores results in the disappearance of all discrete emission lines. The PL shifts are correlated with a substantial increment of Si–OH groups adsorbed on the frustule surface, as revealed by Fourier transform infrared spectroscopy. Copyright © 2014 John Wiley & Sons, Ltd.